Copyright Aware: What You Need to Know - Brunet, Mélanie; Mollel, Obianuju (Université d'Ottawa | University of Ottawa, 2019)
Continuing education workshop delivered at the Canadian Health Libraries Association Conference, June 4, 2019 in Ottawa. Includes presentations slides, quiz, scenario roadmap, and handout of selected teaching and learning resources. Also available in French as "Le droit d'auteur : ce que vous devez savoir".
Keywords: Copyright